2019
DOI: 10.1161/jaha.118.010689
|View full text |Cite
|
Sign up to set email alerts
|

Whether Pulmonary Valve Replacement in Asymptomatic Patients With Moderate or Severe Regurgitation After Tetralogy of Fallot Repair Is Appropriate: A Case‐Control Study

Abstract: Background Although right ventricular ( RV ) volume was significantly decreased in symptomatic patients with repaired tetralogy of Fallot ( rTOF ) after pulmonary valve replacement ( PVR ), RV size was still enlarged along with RV dysfunction. Methods and Results A prospective case‐control study was conducted in a tertiary hospital; 81 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Although right ventricle size decreases and functional class improves after pulmonary valve replacement, right ventricular normalization does not occur very often and modest amount of patients achieve increased systolic function [2,5,7,13,14,16,[21][22][23][24][25][26]. We failed to observe any significant change in the right ventricle measurements after pulmonary valve replacement, only TAPSE and right ventricular outflow tract gradient increased significantly.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Although right ventricle size decreases and functional class improves after pulmonary valve replacement, right ventricular normalization does not occur very often and modest amount of patients achieve increased systolic function [2,5,7,13,14,16,[21][22][23][24][25][26]. We failed to observe any significant change in the right ventricle measurements after pulmonary valve replacement, only TAPSE and right ventricular outflow tract gradient increased significantly.…”
Section: Discussionmentioning
confidence: 76%
“…Marked right ventricle enlargement and dysfunction can be present before the onset of symptoms, which explains the discouraging outcomes in some of the symptomatic patients. Hence, early intervention in asymptomatic patients is advocated [4,7]. Assuming that the less severe the ventricular dilatation prior to valve replacement, the more likely the ventricle will remodel, many investigators tried to determine the right ventricle measurements beyond which return to normal size is unlikely [5,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…A propensity-matched cohort from the INDICATOR registry showed no advantage in adverse effects in the group undergoing PVR, although with the limitations of retrospective matching [ 6 ]. In a recent small non-controlled trial, PVR was associated with fewer adverse events in an asymptomatic population with moderate PV regurgitation [ 7 ]. The question of long-term benefits, or harms, with PVR in rToF and the timing, early versus delayed, is still open to debate.…”
Section: Introductionmentioning
confidence: 99%
“…Longstanding PR results in right ventricular (RV) dysfunction, prolongation of QRS duration, supraventricular and ventricular arrhythmias, and reduced life expectancy. [ 1 2 3 4 5 6 7 8 9 10 11 12 13 ] Therefore, symptomatic chronic PR is an indication for pulmonary valve replacement (PVR). However, studies have shown that even after PVR, there is no significant improvement in the uncorrected RV ejection fraction (UnRVEF) and the corrected RVEF also improves only to the extent of preoperative UnRVEF.…”
Section: Introductionmentioning
confidence: 99%